PERENCANAAN PERAWATAN MESIN PULVERIZER PADA PEMBANGKIT LISTRIK TENAGA UAP MENGUNAKAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) - Novi Nur Hidayanti; Said Salim Dahda (LPPM Politeknik LP3I Medan, 2021)
Competition between companies today requires companies to continue to improve by improving the industrial system. Machine reliability is one of the programs to increase the competitiveness of a company in meeting consumer demand. The pulverizer machine is a very important supporting machine for producing electricity. The pulverizer has several components that are often damaged, such as the coal feeder, gearbox, hydraulic pump, and grinding roller, which causes the production process to experience downtime. This research is about planning the maintenance of machine components. This problem will be solved by using the FMEA approach with Reliability Centered Maintenance (RCM) to determine the failure mode and the effect of failure on critical components. There is 1 failure mode that has the highest Risk Priority Number value. The failure mode is a torn V-Belt. The results of the MTTR and MTTF calculations are used to determine the time interval for the torn V-Belt failure mode, the MTTF value is 735.32 hours or 30.6 days, MTTR is 44.84 hours or 1.8 days. Recommendations for appropriate action through the Task Selection V-Belt failure mode fall into category A, namely Safety Problem with Time Directed (TD) action and optimal scheduling planning of 15 days. Keywords : Scheduling, Failure Mode and Effect Analysis, Reliability Centered Maintenance, Task Selection, TDM